The Timor Sea dispute a note on the process, resolution, and application in the West Philippine Sea (2020)
In order to avoid conflicts arising from competing claims, states have endeavored to conclude maritime delimitation agreements. This, however, is a long and arduous process. Thus, in the interregnum, many have resorted to provisional agreements to benefit from the resources derived from contested areas. In cases where states fail to settle disputes through bilateral negotiations, resort has been made to procedures entailing binding decisions, such as arbitration or litigation. Nevertheless, recourse to these modes of settling disputes is not always available to the parties in maritime boundary disputes. For one, states have often excepted themselves from dispute settlement systems. In this regard, conciliation offers a viable method for resolution along with enquiry and mediation. This article submits that the use of provisional agreements and the conciliation procedure arguably contributed to settling the competing claims of Timor-Leste and Australia as to the Timor Sea and may thus offer a solution to similar disputes. This article details the process and outcome of the resolution of the Timor Sea dispute and questions whether the same may be done in the
West Philippine Sea.
Keywords: Philippines--Boundaries--China; Boundary disputes -- Western Pacific